1994
DOI: 10.1021/ma00085a049
|View full text |Cite
|
Sign up to set email alerts
|

Selective Localization of Carbon Black in Immiscible Polymer Blends: A Useful Tool To Design Electrical Conductive Composites

Abstract: Introduction. It is well-known that the electrical resistivity of insulating polymers can be decreased by dispersing a conductive filler, e.g., carbon black (CB) throughout the polymer matrix.1-7 The critical amount of filler necessary to build up a continuous conductive

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
287
0
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 410 publications
(299 citation statements)
references
References 5 publications
10
287
0
2
Order By: Relevance
“…Therefore, CNFs are not distributed in PS phase, but rather in HDPE phase of the nanocomposite. A similar preferential dispersion of fillers in HDPE phase has also been found in the PE/PS composites reinforced with carbon black particles [9][10][11][12]. The main reason for preferential dispersion of the fillers in HDPE phase is the large melt viscosity of PE compared to that of PS.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…Therefore, CNFs are not distributed in PS phase, but rather in HDPE phase of the nanocomposite. A similar preferential dispersion of fillers in HDPE phase has also been found in the PE/PS composites reinforced with carbon black particles [9][10][11][12]. The main reason for preferential dispersion of the fillers in HDPE phase is the large melt viscosity of PE compared to that of PS.…”
Section: Introductionsupporting
confidence: 72%
“…The percolation concentration is determined to be 1.1 vol%, being smaller than that of the PS/CNF composites of 1.7 vol%. During compounding of PS/CNF master batch and HDPE pellets, CNFs cannot migrate from PS into HDPE phase, because they need sufficient energy to surmount the HDPE/PS interfacial free energy barrier [9][10][11][12]. Therefore, CNFs still reside in PS phase.…”
Section: Introductionmentioning
confidence: 99%
“…Unexpectedly, with the introduction of 15 phr nano-TiO 2 particles into the blend of PLLA/10PU, the size of the PU domains increases slightly (Figure 1b). This result is opposite to that usually seen in polymer blends filled with other nanofillers, such as silicon dioxide (SiO 2 ), clay and multi-walled carbon nanotubes (MWCNTs), where the size of dispersed-phase domains decreases significantly with adding small amounts of nanofillers [43][44][45]. Recently, Cai et al [46] confirmed that morphology evolution of immiscible polymer blends is strongly dominated by the self-agglomerating pattern of nanoparticles in polymer melts.…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 95%
“…The critical exponent's value is smaller than the universal value for a three-dimensional percolating system (t ¼ 1.94) [22]. As reported by Kilbride et al [23], values of t around 1.3 have been observed in polyaniline-PMMA [24,25] or carbon black-polyethylene [26] composites. Recently, t value of 0.97 [27] has been reported for pristine MWNTs (synthesised by CVD approach) and poly(bisphenol A carbonate) (PC) composites prepared by solution blending approach.…”
Section: Electrical Characterisationmentioning
confidence: 66%